Cost of Follow Up After Endovascular Abdominal Aortic Aneurysm Repair in Patients With an Initial Post-Operative Computed Tomography Angiogram Without Abnormalities. (December 2022) - Geraedts, Anna C.M.; van Dieren, Susan; Mulay, Sana; Vahl, Anco C.; Koelemay, Mark J.W.; Balm, Ron; ,; Balm, R.; Elshof, J.W.; Elsman, B.H.P.; Hamming, J.F.; Koelemay, M.J.W.; et al.
Abstract : Objective: The Observing a Decade of Yearly Standardised Surveillance in EVAR patients with Ultrasound or CT Scan (ODYSSEUS) study was conducted to assess differences in outcomes of patients with continued or discontinued yearly follow up after endovascular abdominal aortic aneurysm repair (EVAR). Earlier results of this study showed that discontinued follow up was not associated with poor outcomes. Therefore, an incremental cost analysis and budget impact analysis of de-implementation of yearly imaging following EVAR was performed. Methods: In total, 1 596 patients from the ODYSSEUS study were included. The expected cost savings were assessed if yearly imaging was reduced in patients with a post-operative computed tomography angiogram without abnormalities made around 30 days after EVAR. Costs were derived from the Dutch costs manual, benchmark cost prices, and literature review. Costs were expressed in euros (€) and displayed at 2019 prices. Sensitivity analysis was performed by varying costs. Results: A difference of 24% in cost was found between patients with continued and discontinued imaging follow up. The cost per patient was €1 935 in the continued group vs. €1 603 per patient in the discontinued group at five years post-EVAR, with a mean difference of €332 (95% bias corrected and accelerated bootstrap confidence interval –741 to 114). De-implementation of yearly imaging would result in an annual nationwide cost saving of €678 471. Sensitivity analysis with variation in adherence rates, imaging, or secondary intervention costs resulted in a saving of at least €271 388 per year. Conclusion: This study provided an in depth analysis of hospital costs for post-EVAR patients in the Netherlands with a modest impact on the Dutch healthcare budget.